2022
DOI: 10.1039/d2ra05690a
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition performance of halogen-substituted benzaldehyde thiosemicarbazones as corrosion inhibitors for mild steel in hydrochloric acid solution

Abstract: Halogen-substituted benzaldehyde thiosemicarbazone derivatives were synthesized and applied as corrosion inhibitors for mild steel in 1 M HCl using experimental and computational methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…Furthermore, Table 8 provides data regarding thiosemicarbazones inhibitors reported in literature with structural similarities to HBC and HAC, along with their respective inhibition efficiencies. The inhibition efficiency of HBC and HAC against mild steel alloy corrosion was found to be comparable to, and in some instances even superior to, several other inhibitors 24 – 26 . The HBC and HAC inhibitors in this study demonstrated higher efficiency (96.26% and 95.97%) compared to the previously listed organic inhibitors (91.8%, 93.2%, 92.8%, 94.3%, 92.5%, 93.7%, 94.1% and 94.3%).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, Table 8 provides data regarding thiosemicarbazones inhibitors reported in literature with structural similarities to HBC and HAC, along with their respective inhibition efficiencies. The inhibition efficiency of HBC and HAC against mild steel alloy corrosion was found to be comparable to, and in some instances even superior to, several other inhibitors 24 – 26 . The HBC and HAC inhibitors in this study demonstrated higher efficiency (96.26% and 95.97%) compared to the previously listed organic inhibitors (91.8%, 93.2%, 92.8%, 94.3%, 92.5%, 93.7%, 94.1% and 94.3%).…”
Section: Resultsmentioning
confidence: 67%
“…Furthermore, Honghong Zhang and colleagues synthesized novel halogen-substituted benzaldehyde thiosemicarbazone derivatives and assessed their efficacy as corrosion inhibitors for mild steel in 1 M HCl. The research demonstrated a direct relationship between concentration and inhibitory effectiveness, reaching a peak of 94.3% at a concentration of 400 × 10 –6 M 26 . Some publications primarily focus on electrochemical assessments, offering only a superficial examination of structural elements.…”
Section: Introductionmentioning
confidence: 85%
“…The equivalent circuit utilized for fitting the impedance data is seen in (Figs. 5). The solution resistance and polarization resistance are represented, respectively, by Rs and Rp (which equal the sum of Rct and Rf which represents the resistance of the film created on the metal) and CPE represents the constant phase element.…”
Section: Eis Analysismentioning
confidence: 99%